Timing of ophiolite obduction in the Grampian orogen - Chew, D.; Daly, J.; Magna, T.; Page, L.; Kirkland, Chris; Whitehouse, M.; Lam, R. (Geological Society of America, 2010)
This study addresses the timing and pressure-temperature (P-T) conditions of ophiolite obduction, one of the proposed causes of the ca. 470 Ma Grampian orogeny of Scotland and Ireland. This event gave rise to the main structural and metamorphic characteristics of the Grampian terrane-the type area for Barrovian metamorphism, the cause of which remains enigmatic despite a century of research. Zircons from the Highland Border ophiolite, Scotland, define a 499 ± 8 Ma U-Pb concordia age, which is interpreted as dating magmatism. Its metamorphism is dated by a 490 ± 4 Ma 40Ar-39Ar hornblende age, and a 488 ± 1 Ma 40Ar-39Ar muscovite age from a metasedimentary xenolith within it, from which P-T estimates of 5.3 kbar and 580 °C relate to ophiolite obduction. Meta-morphism of the Deerpark complex ophiolitic mélange (Irish correlative of the Highland Border ophiolite) is constrained by a 514 ± 3 Ma 40Ar-39Ar hornblende age, while mica schist slivers within it yield detrital zircon U-Pb ages consistent with Laurentian provenance and Rb-Sr and 40Ar-39Ar muscovite ages of ca. 482 Ma. P-T values of 3.3 kbar and 580°C for the mica schist constrain the conditions of ophiolite obduction. Metamorphic mineral ages from the Grampian terrane (Dalradian Supergroup) are substantially younger (ca. 475-465 Ma) than those from the ophiolites. If conductive heating in overthickened crust was the cause of Barrovian metamorphism, then collisional thickening must have started soon after ophiolite obduction at ca. 490 Ma in order to generate the ca. 470 Ma metamorphic peak in the Grampian terrane. © 2010 Geological Society of America.